Self-assembly of colloidal particles into amorphous photonic crystals - Hu‡, Yang; Zhang‡, Yuqi; Yang, Dongpeng; Ma, Dekun; Huang, Shaoming (Materials advances, 2021)
Colloidal photonic crystals (PCs) have been extensively investigated since they can be prepared in an efficient and low-cost way. Different from the conventional PCs with highly ordered structures, amorphous photonic crystals (APCs) with an isotropic photonic bandgap and non-iridescent structural colors have attracted growing interest especially in pigments, angle-independent displays, and optical coatings. This review focuses on the various strategies used for the fabrication of APCs by spraying, infiltration, layer-by-layer deposition, electrolyte-induced assembly, electrophoretic deposition, phase separation, assembly of bi-disperse-suspension, assembly of particles with a rough surface, assembly of soft particles, and assembly of low-charged particles. Their potential applications are also summarized, such as angle-independent displays, sensors, paintings, anti-counterfeiting labels, information storage, and so on. Finally, we present our perspectives together with the challenges of APCs. This review focuses on the introduction, fabrication, and applications of amorphous photonic crystals.